Peran Guru Dalam Penerapan Sekolah Ramah Anak Di Sd Muhammadiyah 16 Surakarta - Septiyan Dwi Cahyono, Risal; Drs.H. Rubino Rubiyanto, M.Pd (2017)
Abstract This study aims to describe (1) the role of teachers in the implementation of child-friendly schools in SD Muhammadiyah 16 Surakarta. (2) the implementation of child-friendly schools in SD Muhammadiyah 16 Surakarta. (3) obstacles faced by teachers in the implementation of child-friendly schools At SD Muhammadiyah 16 Surakarta. (4) Solutions from obstacles faced by teachers in the implementation of child-friendly schools At SD Muhammadiyah 16 Surakarta. This research is a descriptive qualitative research. Technique of collecting data in this research is by interview, observation and documentation. Checking the validity of this data using source and technique triangulation. The results of this study indicate that: (1) the role of teachers in the implementation of friendly schools include: the role of teachers as educators, the role of teachers as teachers, the role of teachers as mentors, the role of teachers as trainers and the role of teachers as advisors. (2) the implementation of child-friendly schools in SD Muhammadiyah 16 Surakarta among others: the beginning of the elimination of punishment culture that does not educate, not discriminate, make learning comfortable and fun, and involve students actively in learning activities. (3) obstacles faced by teachers in the implementation of child-friendly schools include: lack of understanding of teachers about child-friendly school programs and unsupported infrastructure (4) Solutions from obstacles faced by teachers in the implementation of child-friendly schools include: Schools are trying to bring in child friendly school facilitators and attend workshops on child friendly schools. Keywords: role of teacher, child friendly school